Extending the extended self: a mediational-constitutional proposal. - Prezioso, Emanuele; Parisi, Francesco (Synthese, 2025)
This paper explores the mediational and constitutional role of technical images (both analogue and digital) for the definition and continuity of the sense of self, proposing a new framework within the extended mind theory grounded in recent approaches to memory. Traditional cognitive science often views the mind as confined within the brain, but we argue that cognition is not merely extended but fundamentally constituted through ongoing material engagements with technical images within specific sociocultural contexts. Our interdisciplinary approach integrates cognitive archaeology, media theory, and cognitive sciences, emphasising the dynamic, embodied, and situated nature of cognition. This perspective shifts the understanding of the mind from a static, internal entity to a dynamic, distributed process continually mediated through organismic transactions in the environment. Building on this tradition of studies in the extended mind, we introduce the Mediational-Constitutional Principle, arguing that technical images not only trigger cognitive processes but actively constitute them. In the paper, we illustrate how technical images mediate and constitute the sense of self because they are central in how memory is continually re-enacted in specific sociomaterial environments made of people, things, and practices. These images function as automatic ecological records, blending past and present, influencing personal narratives and memory.